2018
DOI: 10.1136/rmdopen-2018-000739
|View full text |Cite
|
Sign up to set email alerts
|

Neutropaenia in early rheumatoid arthritis: frequency, predicting factors, natural history and outcome

Abstract: ObjectivesTo determine the frequency, severity and natural history of neutropaenia in early rheumatoid arthritis (RA), explore its associations with clinical features and assess its impact on clinical management.MethodsThe Scottish Early Rheumatoid Arthritis inception cohort prospectively recruited patients with newly diagnosed RA and followed them up every 6 months. Patients with RA who developed at least one episode of neutropaenia (grade 1: <2.0×10^9/L; grade 2: <1.5×10^9/L; grade 3: <1.0×10^9/L; grade 4: <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…One clinical problem which potentially may influence prognosis in lymphoma is treatment-related neutropenic fever [34][35][36][37]. It is well known that patients with AIDs such as RA and SLE have an increased risk of infections [34,35] and neutropenia may be a manifestation of some of the AIDs [36][37][38], but it is not known if neutropenic fever is a more common problem in DLBCL patients with a concomitant AID than in DLBCL patients in general.…”
Section: Introductionmentioning
confidence: 99%
“…One clinical problem which potentially may influence prognosis in lymphoma is treatment-related neutropenic fever [34][35][36][37]. It is well known that patients with AIDs such as RA and SLE have an increased risk of infections [34,35] and neutropenia may be a manifestation of some of the AIDs [36][37][38], but it is not known if neutropenic fever is a more common problem in DLBCL patients with a concomitant AID than in DLBCL patients in general.…”
Section: Introductionmentioning
confidence: 99%
“…For thiopurines there were nine retrospective cohort studies, 45 48–50 52 54 56–58 six case–control studies, 47 55 59–62 two prospective cohort studies, 46 53 and one RCT. 51 Other conventional DMARDs were studied in 13 retrospective cohort studies, 18 20 21 24 25 27 29–32 34 35 37 39 40 44 2 case–control studies, 23 36 7 prospective cohort studies, 19 33 38 41–43 1 RCT reanalysed as a cohort 22 and 2 additional RCTs. 26 28 Of those studies on MTX that reported concomitant medication, all participants were taking folic acid in six studies, 20 22 31 38 39 41 42 while some but not all participants were taking folic acid in five further studies.…”
Section: Resultsmentioning
confidence: 99%
“… 67 There was moderate-quality evidence that leucopaenia or low neutrophil count at baseline were associated with increased risk of neutropenia in those prescribed conventional DMARDs +/− biologics. 23 …”
Section: Study Findingsmentioning
confidence: 99%
“…As SERA is an inception cohort, all participants started on conventional DMARDs 21 prescribed in primary care, with only 8% of participants receiving biologics after a mean follow-up period of 18 months. 39 This could lead to an underestimation of absolute costs across LTC groups since biologics are much more expensive than conventional DMARDs.…”
Section: Discussionmentioning
confidence: 99%
“…In line with national guidelines and standard clinical practice, patients with RA have to fail at least two conventional synthetic DMARDs before starting a biological DMARD. As SERA is an inception cohort, all participants started on conventional DMARDs21 prescribed in primary care, with only 8% of participants receiving biologics after a mean follow-up period of 18 months 39. This could lead to an underestimation of absolute costs across LTC groups since biologics are much more expensive than conventional DMARDs.…”
Section: Discussionmentioning
confidence: 99%